Project-Management in Practice A Guideline and Toolbox for Successful Projects - Alam, M. Daud; Gühl, Uwe F. (Springer Berlin Heidelberg : Imprint: Springer, 2016)
This practice-oriented book explores a variety of cross-project topics and specific aspects of different project phases. It also offers tips, examples, templates and checklists, and discusses concrete problems and solutions from project practice in IT and the automotive industry. The authors combine their extensive practical experience in years of project work with relevant project-management theory. Each chapter begins with a list of the learning objectives and concludes with a summary of the insights provided. Accordingly, the book offers a valuable resource for: Beginners wishing to acquire basic project management skills Participants in more advanced project management training who are looking for instructional material Project management experts who want to learn about further aspects, and to employ templates and checklists for even more successful projects.